2020
DOI: 10.5194/adgeo-53-1-2020
|View full text |Cite
|
Sign up to set email alerts
|

Successful practice in early career networks: insights from the polar sciences

Abstract: Abstract. Acquiring not only field-specific knowledge but also a set of transferable professional skills becomes increasingly important for Early Career Scientists (ECS) in Geosciences and other academic disciplines. Although the need for training in transferable skills adds to the work-load of an individual Early Career Scientist, it is often neglected within the traditional academic environments. International Early Career Networks (ECN) are global voluntary communities of early career scientists aiming (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, as stated in Sobey et al (2013) "most networking opportunities are found at higher levels." We (the MEASO ECR community) encourage ECRs to engage in mentoring programmes, research groups within their community and seek sponsors who can enhance their confidence, visibility, credibility, and professional networks (Ansmann et al, 2014;Fenton et al, 2016;Gottlieb and Travis, 2018;Bohleber et al, 2020). The academic environment has changed rapidly over the last decades (Pitt and Mewburn, 2016), and the issues ECRs face now are most likely different from those their mentors faced earlier in their careers.…”
Section: Pressure To Networkmentioning
confidence: 99%
“…However, as stated in Sobey et al (2013) "most networking opportunities are found at higher levels." We (the MEASO ECR community) encourage ECRs to engage in mentoring programmes, research groups within their community and seek sponsors who can enhance their confidence, visibility, credibility, and professional networks (Ansmann et al, 2014;Fenton et al, 2016;Gottlieb and Travis, 2018;Bohleber et al, 2020). The academic environment has changed rapidly over the last decades (Pitt and Mewburn, 2016), and the issues ECRs face now are most likely different from those their mentors faced earlier in their careers.…”
Section: Pressure To Networkmentioning
confidence: 99%
“…Brasier et al defined ECRs as 'researchers within 5 years of a terminal degree' (2020: 2) or as '0-5 years Post-PhD' while describing mid-career researchers as '5-10 years Post-PhD' (Ibid: 3). Bohleber et al (2020) offered a more comprehensive definition of ECRs as 'university students (bachelor, master and PhD students), postdoctoral researchers and Early Career professionals (assistant professor or lecturer, research associate)'. They also stated that 'the European Union considers the time limit to apply for a starting grant no longer than 7 years after PhD completion.…”
Section: Who Are Early Career Researchers and Why Does It Matter?mentioning
confidence: 99%